2008
DOI: 10.1088/0953-4075/41/19/195204
|View full text |Cite
|
Sign up to set email alerts
|

Doubly excited states of ammonia produced by photon and electron interactions

Abstract: The formation and decay of doubly excited ammonia produced by photon and electron interactions have been investigated through measuring (i) the cross sections for the emission of the Lyman-α fluorescence in the photoexcitation of NH3 as a function of incident photon energy in the range 15–60 eV and (ii) the electron-energy-loss spectrum of NH3 tagged with the Lyman-α photons at 100 eV incident electron energy and 8° electron scattering angle in the range of the energy loss 15–48 eV. Six superexcited states hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Bands in the one-photon absorption spectrum observed at 18.4 eV and at 30-33 eV previously assigned to double excitations involving Rydberg transitions are reassigned to the valence single-excitation resonances ns* E and a combination of s Es* E and s Es* A , respectively. The 18.4 eV band had been previously assigned 114 as n -3s, n -? and presumed to be associated with the IP observed at 24 eV that is assigned 119 to the double excitation n -3s, n -N. Properties of the diabatic model are key to this reassignment as the n -3s, n -3s excitation dr is found to be counter-intuitively at higher energies than n -3s, n -N and ca.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bands in the one-photon absorption spectrum observed at 18.4 eV and at 30-33 eV previously assigned to double excitations involving Rydberg transitions are reassigned to the valence single-excitation resonances ns* E and a combination of s Es* E and s Es* A , respectively. The 18.4 eV band had been previously assigned 114 as n -3s, n -? and presumed to be associated with the IP observed at 24 eV that is assigned 119 to the double excitation n -3s, n -N. Properties of the diabatic model are key to this reassignment as the n -3s, n -3s excitation dr is found to be counter-intuitively at higher energies than n -3s, n -N and ca.…”
Section: Discussionmentioning
confidence: 99%
“…Absorption at 16.3 eV and 25.3 eV is also observed to Rydberg bands leading up to the ionization potentials for s E -N and s A -N at 16.4 and 27.3 eV, respectively. 114 Two other broad bands are also observed centred at 18.4 eV and 31.5 eV, although originally only part of the 18.4 eV band was in the observable range and so this band was first assigned at 22 eV whilst the higher-energy band was observed partially resolved into components at 30 eV and 33 eV. 64 Both systems were attributed to double excitations, despite the typically low oscillator strength for such bands in one-photon spectroscopy.…”
Section: (C) Reduction To An Effective 2-state Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies, it has been shown that the multiply excited states are well probed by fluorescence photons emitted by fragments produced through the neutral dissociations (process (4)). Several doubly excited states of CH 4 , NH 3 and H 2 O were revealed in photoexcitation by measuring the cross sections for the emission of the Lyman-α, Balmer series and radical fluorescences as a function of the incident photon energy [7][8][9][10][11][12]. These authors found much larger cross sections due to doubly excited states than those expected within the independent electron model.…”
Section: Abmentioning
confidence: 98%